Representation of Practice Guidelines with XML – Modeling with XML Schema - Hoelzer, S.; Schweiger, R.; Dudeck, J. (Methods of Information in Medicine, 2002)
Objectives: Data and information in medicine are mainly represented in slightly structured or even unstructured, narrative text documents. It is nearly impossible to detect and handle relationships between data elements within narrative documents or to retrieve parts of documents that contain specific information. But information access and retrieval are essential to serve the delivery and application of evidence-based medicine.Methods: The eXtensible Markup Language (XML) provides a standard means to explicitly describe a document‘s structure and to identify meaningful elements inside textual narrations. Information about the state-of-the-art medical care can be delivered to the physician by different means and media. Clinical practice guidelines are thought to be one possible solution to summarize and present current medical evidence.Results: The structuring of resources containing medical information with XML can facilitate the provision of problem-specific medical information at the point of care by improving content retrieval and presentation. In our project, the XML Schema is used for the electronic representation in order to structure guidelines (and other text-based resources) in a standardized way.Conclusion: The transition from unstructured textual data towards structured and coded data will be a migration process. One of the premises of our approach is that the structure that is defined by the information model doesn‘t restrict the content of the documents. This approach may fill the gap between computerized, algorithmic guideline recommendations and text-based guideline distributions.
Keywords: XML; clinical practice guidelines; schema; modeling